Autorzy:Wojciech Babiański , Lech Chańko, Joanna Czarnowska
Wydawnictwo:Nowa Era
Rok wydania:2014
Określ stopień sumy 4.43 gwiazdek na podstawie 7 opinii

`a)` 

`u(x)+w(x)=(px^4+x-1)+(x^4+x^2+1)=px^4+x-1+x^4+x^2+1=(p+1)x^4+x^2+x`  

 

`{("st"(u+w)=4,\ \ \ "gdy"\ \ \ p+1ne0), ("st"(u+w)=2,\ \ \ "gdy"\ \ \ p+1=0):} \ \ \ =>\ \ \ {("st"(u+w)=4,\ \ \ "gdy"\ \ \ pne-1), ("st"(u+w)=2,\ \ \ "gdy"\ \ \ p=-1):}` 

 

 

`b)` 

`u(x)+w(x)=(px^4+2)+(-2x^4-px^3)=px^4+2-2x^4-px^3=(p-2)x^4+(2-p)x^3=(p-2)x^4+(-(p-2))x^3` 

 

`{("st"(u+w)=4,\ \ \ "gdy"\ \ \ p-2ne0), ("st"(u+w)=0,\ \ \ "gdy"\ \ \ p-2=0):} \ \ \ =>\ \ \ {("st"(u+w)=4,\ \ \ "gdy"\ \ \ pne2), ("st"(u+w)=0,\ \ \ "gdy"\ \ \ p=2):}` 

 

 

`c)` 

`u(x)+w(x)=((p^2-4)x^3+x)+((p-2)x^2+1)=(p^2-4)x^3+x+(p-2)x^2+1=(p^2-4)x^3+(p-2)x^2+x+1` 

 

`{("st"(u+w)=3,\ \ \ "gdy"\ \ \ p^2-4ne0\ \ \ "i"\ \ \ p-2ne0), ("st"(u+w)=2,\ \ \ "gdy"\ \ \ p^2-4=0\ \ \ "i"\ \ \ p-2ne0),("st"(u+w)=1,\ \ \ "gdy"\ \ \ p^2-4=0\ \ \ "i"\ \ \ p-2=0):}\ \ \ =>\ \ \ {("st"(u+w)=3,\ \ \ "gdy"\ \ \ p^2ne4\ \ \ "i"\ \ \ pne2), ("st"(u+w)=2,\ \ \ "gdy"\ \ \ p^2=4\ \ \ "i"\ \ \ pne2),("st"(u+w)=1,\ \ \ "gdy"\ \ \ p^2=4\ \ \ "i"\ \ \ p=2):}\ \ \ =>\ \ \ {("st"(u+w)=3,\ \ \ "gdy"\ \ \ pne-2\ \ \ "i"\ \ \ pne2), ("st"(u+w)=2,\ \ \ "gdy"\ \ \ p=-2),("st"(u+w)=1,\ \ \ "gdy"\ \ \ p=2):}`